2017
DOI: 10.1024/0301-1526/a000627
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction – overview from a cardiovascular perspective

Abstract: Summary:Erectile dysfunction (ED) is an evolving health problem with growing incidence in the ageing male population with potentially predictive value for cardiovascular and other chronic diseases. ED shares the common cardiovascular risk factors. The aetiology of ED is numerous including neurogenic, psychogenic, arteriogenic, and venogenic reasons. The origin of arteriogenic ED is frequently atherosclerosis. Patients not adequately responding to conservative measures including oral medication are often referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Therefore, it promotes the release of cytokines, chemokines and dilating hormones 31,34,35 , which facilitates the transfer and migration of leukocytes to the lesion site 3638 . Erectile dysfunction (ED) and cardiovascular diseases share the same risk factors 39 . As an example, the sustained presence of low-grade inflammatory mediators in patients with ED and coronary artery diseases is well documented 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it promotes the release of cytokines, chemokines and dilating hormones 31,34,35 , which facilitates the transfer and migration of leukocytes to the lesion site 3638 . Erectile dysfunction (ED) and cardiovascular diseases share the same risk factors 39 . As an example, the sustained presence of low-grade inflammatory mediators in patients with ED and coronary artery diseases is well documented 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HCY is also identified to be a useful marker for CVD 26 27. Meanwhile, ED could be a potentially predictive factor for cardiovascular and other chronic diseases 28. Based on the relevance, it was assumed that HCY might be a risk factor for ED 8 9…”
Section: Discussionmentioning
confidence: 99%
“…4 Arterial insufficiency is the leading cause of ED and may result from obstructions of the common and internal iliac arteries as well as the pudendal and penile arteries. 5 It was recently shown that the pudendal artery is the single most frequent arterial segment to be affected by atherosclerotic obstructions in patients with ED of arterial origin. 6 In that study, the average pudendal arterial diameter was very comparable to the average coronary artery diameter.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with ED attributed to arterial disease, endovascular therapy constitutes promising results to restore blood flow and improve clinical outcomes. 5,7,8 However, the ideal antirestenotic regimen within this challenging arterial segment remains to be determined. 7 Given that ED with arterial obstructions of oftentimes small-caliber erection-related arteries may be present even in comparatively young patients, a "leave nothing behind strategy" with drug-coated balloon (DCB) angioplasty may be a favorable treatment option.…”
Section: Introductionmentioning
confidence: 99%